P133 Ecological Interventions for Health Outcomes. (13th September 2016) - de Bell, S; Graham, H; White, P
Abstract : Background: Evidence linking exposure to green and blue spaces to mental health and wellbeing is increasing policy interest in interventions to improve these spaces. However, studies rarely consider their biological quality pre- and post-intervention. This is an interdisciplinary study using a river restoration project to assess the impact of the restoration on ecological health and self-reported health at a local level. Methods: The river Medlock, Manchester, has recently been restored to a semi-natural state but remains culverted through much of its length. The river Irk flows through areas with similar demographics to the Medlock but has not been restored so forms a comparison. Macroinvertebrate samples are being collected from the rivers to investigate whether the restoration has caused a change in the water quality. A sample of 12 people, all users of urban green space along the rivers, were recruited to participate in focus groups; topics included local people's use of green space, their preferences in natural environments, and the impact of the restoration on the health and well-being of the community. The focus groups were audio-recorded, transcribed, and analysed thematically. Results: Analyses are ongoing but initial data show that the restored section of the river Medlock is more biodiverse than its unrestored comparator. Key themes arising from the focus groups include the importance of urban parks as spaces for relaxation and stress reduction and the value placed on being able to view water in these spaces. The majority of people reported positive opinions of the river restoration and its impact on the benefits they derived from the spaces. Conclusion: The restoration has improved the ecological health of the river and has had positive effects on the benefits people gain from visits to local green spaces. This study adds to the evidence base for environment and health research by investigating relationships between changes in ecological health and public health, it is relevant to policy makers as it indicates that policies to protect and conserve the natural environment could have health co-benefits.